The Optimalisasi Pemberian Edukasi tentang Dampak Hipertensi pada Lansia di Daerah Rawan Bencana Banjir - Noorratri, Erika Dewi; Wahyuni, Wahyuni; Mustikasari, Irma (Jurnal Pengabdian Harapan Ibu (JPHI), 2025)
The Community service is carried out in flood-prone areas in the working area of Purwodiningratan Health Centre Surakarta, by providing health education about the impact of hypertension on the elderly who suffer from hypertension. Elderly people suffering from hypertension in flood-prone areas need to gain knowledge about the impact caused if hypertension is not treated, because flooding makes a person think more and feel the impact so that it can cause a person's blood pressure to rise. Lack of understanding of the impact of hypertension can lead to complications from hypertension which have more serious consequences. The purpose of this extension is to provide additional knowledge to the elderly about the impact of hypertension and prevent complications from hypertension in flood-prone areas and increase awareness of healthy living behaviour in the community. The method used is providing counselling using the lecture method, providing material with leaflets. The results of the service activities are seen from the results of the pre-test 14% do not understand and post-test 93% of residents understand and understand the material presented. So it can be concluded that there is an increase in knowledge about the impact of hypertension.